Taking Control: The Efficacy and Durability of a Peer-Led Uncertainty Management Intervention for People Recently Diagnosed With HIV. Issue 1 (2nd January 2017) - Brashers, Dale E.; Basinger, Erin D.; Rintamaki, Lance S.; Caughlin, John P.; Para, Michael
ABSTRACT: HIV creates substantial uncertainty for people infected with the virus, which subsequently affects a host of psychosocial outcomes critical to successful management of the disease. This study assessed the efficacy and durability of a theoretically driven, one-on-one peer support intervention designed to facilitate uncertainty management and enhance psychosocial functioning for patients newly diagnosed with HIV. Using a pretest–posttest control group design, 98 participants received information and training in specific communication strategies (e.g., disclosing to friends and family, eliciting social support, talking to health care providers, using the Internet to gather information, and building social networks through AIDS service organizations). Participants in the experimental group attended six 1-hour sessions, whereas control participants received standard of care for 12 months (after which they received the intervention). Over time, participants in the intervention fared significantly better regarding (a) illness uncertainty, (b) depression, and (c) satisfaction with social support than did those in the control group. Given the utility and cost-effectiveness of this intervention and the uncertainty of a multitude of medical diagnoses and disease experiences, further work is indicated to determine how this program could be expanded to other illnesses and to address related factors, such as treatment adherence and clinical outcomes.